Perancangan Soal Literasi Numerasi: Komponen dan Faktor yang Mempengaruhi Kinerja Guru - Sarumaha, Yenny Anggreini; Rizkianto, Ilham (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Reading literacy and mathematics literacy are important focuses in the Minimum Competency Assessment launched by the government. This study aims to provide an overview of how teachers in schools design numeracy literacy questions and factors that affect the design process. The subjects in this study are 14 subject teachers at one of the Tsanawiyah Madrasah in Sleman, Yogyakarta. The data collected were in the form of teacher designs, field notes, and interview results. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the question design made by the teacher, it can be seen that most teachers choose to design reading literacy questions rather than numeracy questions. The content selected in literacy is mostly informational text, while for numeracy the largest content is numbers. The cognitive process that is the goal of most problems in literacy is the process of interpretation and integration, while in numeracy problems most of them are at the level of comprehension. Both literacy and numeracy matters, the dominant context used is the personal and scientific context. The factors that affect the design of numeracy literacy questions are the availability of resources and support, curriculum and assessment factors, time and workload factors, and internal teacher factors